The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/hep.26012
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring bile acid transport in single living cells using a genetically encoded Förster resonance energy transfer sensor

Abstract: Bile acids are pivotal for the absorption of dietary lipids and vitamins and function as important signaling molecules in metabolism. Here, we describe a genetically encoded fluorescent bile acid sensor (BAS) that allows for spatiotemporal monitoring of bile acid transport in single living cells. Changes in concentration of multiple physiological and pathophysiological bile acid species were detected as robust changes in F€ orster resonance energy transfer (FRET) in a range of cell types. Specific subcellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…The molecules that constitute the circulating pool a bile acid binding site (based on the binding site of FXR) and two reporter molecules whose fl uorescence is determined by the extent to which bile acids occupy the binding site, the greater the binding, the less the fl uorescence. The technique, as described by van der Velden et al ( 217 ), uses the well-known Forster resonance energy transfer (FRET) principle, and has already been used to characterize bile acid transport into isolated hepatocytes.…”
Section: Bile Acid Metabolism: Transport and The Enterohepatic Circulmentioning
confidence: 99%
“…The molecules that constitute the circulating pool a bile acid binding site (based on the binding site of FXR) and two reporter molecules whose fl uorescence is determined by the extent to which bile acids occupy the binding site, the greater the binding, the less the fl uorescence. The technique, as described by van der Velden et al ( 217 ), uses the well-known Forster resonance energy transfer (FRET) principle, and has already been used to characterize bile acid transport into isolated hepatocytes.…”
Section: Bile Acid Metabolism: Transport and The Enterohepatic Circulmentioning
confidence: 99%
“…L-FABP also bound other oxidized lipids to protect hepatic cells from oxidative stress (58,85,86,89,90). L-FABP inhibits microsomal sulfation of select bile acids in vitro (70), is essential for bile acid uptake and intracellular transport as evidenced by photoaffinity-labeled bile acid cross-linking studies (15), and decreases bile acid distribution into some intracellular compartments (82). Thus, by binding bile acids in the cytoplasm, L-FABP may act to retain bile acids within the hepatocytes and decrease their excretion into bile via export pumps that concentrate bile acids Ͼ1,000-fold in bile compared with hepatocytes (43).…”
Section: G1138 L-fabp In Murine Hdl-cholesterol/bile Acid Metabolismmentioning
confidence: 99%
“…While SCP-2 also binds cholesterol hydroperoxides, it facilitates, rather than prevents, the toxic effects of these hydroperoxides (39 -41, 84). Analogous to the effects of L-FABPbinding bile acids in the cytosol to reduce bile acid distribution to the nucleus (82), by binding oxysterols the SCP-2 may sequester these ligands in the cytosol and peroxisomes to decrease their availability in the nucleus. This may explain in part why loss of SCP-2/SCP-x increased expression of Cyp7A1 and Cyp27A1, despite unaltered levels of LXR␣.…”
Section: G1138 L-fabp In Murine Hdl-cholesterol/bile Acid Metabolismmentioning
confidence: 99%
“…Recently, Itoh et al developed a smFRET method to monitor the local balance between the guanine nucleotide exchange factors and the GTPase-activating proteins for Rac1 and Cdc42 on the membrane of living cells [92]. In addition, van der Velden et al demonstrated a genetically encoded fluorescent bile acid sensor for spatio-temporal monitoring the transportation of bile acid in single living cell [93]. Tanimura …”
Section: Measurement In Living Cellsmentioning
confidence: 98%